Analysis Of The Relationship Between Vendors’ Characteristics, Knowledge, And Attitudes Towards Preparedness For Fire Hazards In Karangayu Market Semarang - Julia Novitasari; MG Catur Yuantari (Journal Occupational Health Hygiene and Safety, 2026)
Markets as public facilities with high activity have potential fire hazard risks due to electrical installations, flammable materials, and building and visitor density. This study aims to analyze the relationship between characteristics, knowledge, and attitudes with the preparedness of traditional market traders to potential fire hazard risks. This study was conducted from October 2025 to February 2026 using an observational analytical design with a cross-sectional approach on 95 Karangayu market traders determined by the Slovin formula and accidental sampling techniques. Data were collected using questionnaires and observations, then analyzed univariately and bivariately using Spearman's Rank and Eta Association. The results show that respondents were predominantly female (72.6%), with an average age of 45 years and 15 years of trading experience. Statistical results showed a relationship between length of service (p=0.042), knowledge (p=0.001), and attitude (p=0.001) with preparedness, while gender (p=0.961), age (p=0.405), education level (p=0.847), and fire experience (p=0.591) were not related. In conclusion, vendor preparedness is influenced by length of service, knowledge, and attitude. It is recommended that market managers improve fire protection facilities and vendors increase their awareness of potential fire risks.